Recent advances in catalytic carbofluorination of unsaturated system via C–F bond reconstruction - Yaxin Zeng; Xufei Yan; Ying Xia (Tetrahedron Chem)
The distinctive properties of the fluorine atom confer significant advantages to organofluorine compounds in pharmaceuticals, agrochemicals, and materials science. A particularly promising approach for synthesizing these compounds involves atom-economical carbofluorination reactions. These reactions involve the activation of a carbon-fluorine (C–F) bond, then facilitating the incorporation of both a carbon-based fragment and a fluorine atom into an unsaturated system. The capacity to reintegrate the fluorine atom from the starting material into the final product, known as fluoride recycling via C–F bond reconstruction, is advantageous in terms of both atom and step economy. This review highlights recent advancements in catalytic C–F bond reconstruction, encompassing the background, chemical transformations, reaction scope, synthetic applications, mechanisms, and future research directions.